Waveform separation and image fusion for Lamb waves inspection resolution improvement. (April 2016) - Zeng, Liang; Zhao, Ming; Lin, Jing; Wu, Wentao
Abstract: To improve the resolution of Lamb wave inspection, a waveform separation and image fusion strategy is established. The integration of the adaptive Chirplet transform and the time-varying band-pass filtering provides a methodology for extracting interest waveforms from the overall Lamb wave signals. On this basis, image generation and image fusion is employed to establish a visual description of the overall health status of structures. The strategy could be still available even under the conditions where the dispersion characteristics of the structure cannot be correctly estimated and the reference signals are not accessible. The merits of the proposed strategy are demonstrated by an experimental example.